Legal Protection of Personal Data in Combating Cybercrime in Indonesia - Rizal Abidin; Nur Kumala Dewi; Dwi Agung Santoso; Taufan Dwiyogo S; Nanang Sumargo; Cahya Citra Carolene; Triana Asih Wulandari; Muthi'ah Dwita Fathinah (Sean Institute, 2026)
The development of online lending services as part of financial technology has transformed public access to financial services in Indonesia. This convenience has been accompanied by an increasing volume of personal data processing, which raises new concerns regarding information security and privacy protection. Various data breach incidents indicate that personal data protection is no longer limited to administrative issues but is closely related to cybercrime risks within the digital ecosystem. This study aims to analyze the legal liability of online lending providers for personal data violations and to evaluate the effectiveness of data protection regulations in addressing cybercrime. The research employs a normative juridical approach through the analysis of legislation, scholarly literature, and case studies involving the misuse of personal data in online lending services. The findings show that online lending providers, as personal data controllers, bear administrative, civil, and criminal liability in cases of negligence in safeguarding user data. The main challenges in personal data protection include weaknesses in regulatory supervision, complexities in digital evidence procedures, and the low level of public digital literacy.